Ground reaction forces in shallow water running are affected by immersion level, running speed and gender - Haupenthal A.* (2013)
Objectives: To analyze the effect of depth of immersion, running speed and gender on ground reaction forces during water running. Design: Controlled laboratory study. Methods: Twenty adults (ten male and ten female) participated by running at two levels of immersion (hip and chest) and two speed conditions (slow and fast). Data were collected using an underwater force platform. The following variables were analyzed: vertical force peak (Fy), loading rate (LR) and anterior force peak (Fx anterior). Three-factor mixed ANOVA was used to analyze data. Results: Significant effects of immersion level, speed and gender on Fy were observed, without interaction between factors. Fy was greater when females ran fast at the hip level. There was a significant increase in LR with a reduction in the level of immersion regardless of the speed and gender. No effect of speed or gender on LR was observed. Regarding Fx anterior, significant interaction between speed and immersion level was found: in the slow condition, participants presented greater values at chest immersion, whereas, during the fast running condition, greater values were observed at hip level. The effect of gender was only significant during fast water running, with Fx anterior being greater in the men group. Increasing speed raised Fx anterior significantly irrespective of the level of immersion and gender. Conclusions: The magnitude of ground reaction forces during shallow water running are affected by immersion level, running speed and gender and, for this reason, these factors should be taken into account during exercise prescription. © 2012 Sports Medicine Australia.